1991
DOI: 10.1104/pp.96.3.881
|View full text |Cite
|
Sign up to set email alerts
|

Acid and Neutral Invertases in the Mesocarp of Developing Muskmelon (Cucumis melo L. cv Prince) Fruit

Abstract: Acid and neutral invertases were found in the mesocarp of developing muskmelon (Cucumis melo L. cv Prince) fruit and the activities of these enzymes declined with maturation of the fruit, concomitantly with the accumulation of sucrose. Neutral invertase was only present in the soluble fraction and acid invertase was present in both the soluble and cell-wall fractions. The cell-wall fraction contained three types of acid invertase: a NaCI-released invertase; an EDTA-released invertase, and a tightly bound inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 18 publications
2
21
1
1
Order By: Relevance
“…!., Not inhibitthat a reduced sulfhydryl group is not essential for the activity of either enzyme from carrot. This finding is in contrast to previous reports of other neutral and alkaline invertases, which were all inhibited by HgCl 2 (Masuda et al, 1987;Ranwala et al, 1991;Chen and Black, 1992; Van den Ende and Van Laere, 1995). Figure 3.…”
Section: Effects Of Lnhibitorscontrasting
confidence: 99%
See 1 more Smart Citation
“…!., Not inhibitthat a reduced sulfhydryl group is not essential for the activity of either enzyme from carrot. This finding is in contrast to previous reports of other neutral and alkaline invertases, which were all inhibited by HgCl 2 (Masuda et al, 1987;Ranwala et al, 1991;Chen and Black, 1992; Van den Ende and Van Laere, 1995). Figure 3.…”
Section: Effects Of Lnhibitorscontrasting
confidence: 99%
“…The results of earlier studies suggested that the function of these enzymes is the hydrolysis of SUC in the cytoplasm of cells that lack significant amounts of acid invertase activity (Ricardo and ap Rees, 1970). More recent studies have shown the presence of neutral / alkaline and different isoforms of acid invertase in the same tissue (Morell and Copeland, 1984;Masuda et al, 1988;Ranwala et al, 1991). These invertase isoforms, with different subcellular locations and unique biochemical properties, may allow independent control of Suc metabolism, translocation, and storage (Chen and Black, 1992).…”
mentioning
confidence: 99%
“…In contrast, the implication of NIs in fruit development has remained in the background. NIs have long been thought to regulate sucrose metabolism in mature internodes of sugar cane, in sugar beet and carrot roots (reviewed in Ranwala et al 1991) and in peach fruit (Nonis et al 2007), which all store sucrose. The grapevine NIs, for which expression proWles were studied in this paper, are somewhat regulated at transcriptional level in the mesocarp and exocarp of ripening berries that accumulate glucose and fructose.…”
Section: Discussionmentioning
confidence: 99%
“…PaxgINV2 was similarly inhibited by Cu 2+ (3.5%) and Zn 2+ (5.3%). The sensitivity of invertases to these three heavy metals (Cu 2+ , Zn 2+ and Hg 2+ ) has previously been observed in other studies (e.g., Lin and Sung 1993;Masuda et al 1987;Ranwala et al 1991), and it has been suggested that they inhibit activity by interfering with protein thiol groups that are crucial for eVective catalysis (Karuppiah et al 1989). Cysteine, for example, contains a thiol side chain, and as such is vulnerable to the reactivity of Cu 2+ , Hg 2+ and Zn 2+ ions (Belcastro et al 2005).…”
Section: Metal Cation Sensitivitymentioning
confidence: 79%